MODELO ANATÔMICO DO SISTEMA CARDIOVASCULAR DE EQUINO - Dos Santos, Eduarda Nunes; Tesch, Joice; Taquariano, Laura; Linhares, Marcella Teixeira (Salão do Conhecimento, 2019)
Trabalho avaliativo proposto em aula.